GAS SLUG ASCENT THROUGH CHANGES IN CONDUIT DIAMETER: LABORATORY INSIGHTS INTO A VOLCANO-SEISMIC SOURCE PROCESS IN LOW-VISCOSITY MAGMAS - James M.R.; Lane S.J.; Chouet B.A. (My University, 2006)
Seismic signals generated during the flow and degassing of low-viscosity magmas include long-period (LP) and very-long-period (VLP) events, whose sources are often attributed to dynamic fluid processes within the conduit. We present the results of laboratory experiments designed to investigate whether the passage of a gas slug through regions of changing conduit diameter could act as a suitable source mechanism. A vertical, liquid-filled glass tube featuring a concentric diameter change was used to provide canonical insights into potentially deep or shallow seismic sources. As gas slugs ascend the tube, we observe systematic pressure changes varying with slug size, liquid depth, tube diameter, and liquid viscosity. Gas slugs undergoing an abrupt flow pattern change upon entering a section of significantly increased tube diameter induce a transient pressure decrease in and above the flare and an associated pressure increase below it, which stimulates acoustic and inertial resonant oscillations. When the liquid flow is not dominantly controlled by viscosity, net vertical forces on the apparatus are also detected. The net force is a function of the magnitude of the pressure transients generated and the tube geometry, which dictates where, and hence when, the traveling pressure pulses can couple into the tube. In contrast to interpretations of related volcano-seismic data, where a single downward force is assumed to result from an upward acceleration of the center of mass in the conduit, our experiments suggest that significant downward forces can result from the rapid deceleration of relatively small volumes of downward-moving liquid. Copyright 2006 by the American Geophysical Union.